4‐ketoproline: An electrophilic proline analog for bioconjugation. Issue 2 (March 2015) - Choudhary, Amit; Kamer, Kimberli J.; Shoulders, Matthew D.; Raines, Ronald T.
Abstract : Installing an electrophilic amino‐acid residue can engender a peptide or protein with chemoselective reactivity. Such a modification to collagen, which is the most abundant protein in animals, could facilitate the development of new biomaterials. Collagen has an abundance of proline‐like residues. Here, we report on the incorporation of an electrophilic proline congener, (2S)‐4‐ketoproline (Kep), into a collagen‐mimetic peptide (CMP). An ab initio conformational analysis of Kep revealed its potential to be accommodated within a collagen triple helix. A synthetic CMP containing a Kep residue was indeed able to form a stable triple helix. Moreover, the condensation of its carbonyl group with aminooxy‐biotin did not compromise the conformational stability of the triple helix. These data encourage the use of 4‐ketoproline as an electrophilic congener of proline. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 110–115, 2015.